A woman's guide to cannabis eaudiobook Using marijuana to feel better, look better, sleep better-and get high like a lady. - Furrer, Nikki (Tantor Media, 2019)
A woman's handbook to demystifying the world of weed, whether it's being used for pain relief, a moment of calm, or a fit of giggles. Women of all ages are using cannabis to feel and look better. For rookies and experienced marijuana users alike, this lively, information-filled book is just the supportive guide you need to find the right dose to relieve anxiety, depression, and inflammation, and mitigate the onset of dementia and other signs of aging. Plus boost moods, ease aches, even lose weight, and get restful sleep. And a dose just for fun? Well, that works, too! Here's how to navigate the typical dispensary, with its overwhelming options of concentrates, edibles, vape pens, and tinctures. Understand the amazing health-giving compounds found in cannabis—THC, CBD, terpenes, and more—and how to use topicals to reduce pain and give your skin a healthy glow. There's even advice on how not to get high but still reap all the amazing health benefits.